THE STUDY OF COMPARISION OF SUBLINGUINAL VERSUS VAGINAL 25 ΜICRO GRAM OF MISOPROSTOL IN THE INDUCTION OF LABOUR AT TERM - SATYA PRABHA. S,; V.G.KULKARNI,; J.V.KULKARNI,; SREEKANTHA,; YOGESH.B., (International Journal of Pharma and Bio Sciences, 2014)
Induction of labour is initiation of uterine activity by an independent stimulus to achieve vaginal delivery after 28 weeks of gestation before the onset of spontaneous labour. There are various researches contributed various drugs, hormones and chemical agents for effective cervical ripening and induction of labour. Here is a detail study of 25micro gram of misoprostol drug effectiveness comparison in sublinguinal and vaginal routes for the induction of labour.